Use of 2-color flow cytometry to assess radiation-induced genotoxic damage on CHO-KI cells - Luma Ramirez de Carvalho; Letícia Bonfim; Daniel Perez Vieira (Brazilian Journal of Radiation Sciences)
The micronucleus assay is an important technique used to evaluate genotoxic damage of chemical or physical agents (as ionizing radiations) on cells, based on quantification of cells bearing micronuclei, which are fragments derived from damage (breakage) of the DNA. Currently, this technique was updated to an automated approach that relies on plasma membrane dissolution to analyze fluorescent dye-labelled nuclei and micronuclei by flow cytometry. Cell suspensions were irradiated in PBS by a 60Co source in doses between 0 and 16 Gy, and incubated by 72h. Cell membranes were lysed in the presence of SYTOX Green and EMA dyes, so EMA-stained nuclei could be discriminated as from dead cells, and nuclei and micronuclei could be quantified. Amounts of micronuclei (percent of events) in the samples, were found to be proportional to radiation doses, and could be fitted to a linear-quadratic model (R² = 0.993). Only higher doses (8 and 16 Gy) and positive control could induce relevant increases in micronucleus amounts. The incorporation EMA showed an increase in irradiated cells. Mid- to high doses (4, 8 and 16 Gy) induced reduction of cell proliferation. Experiments showed the suitability of the technique to replace traditional microscopy analysis in evaluation of the effects of ionizing radiations on cells, with possibility to use in biological dosimetry.